Firm and product responses to domestic and international regulatory change - Chen, Thomas (2023)
The thesis looks at the effects of domestic and international regulatory change on trade costs and firms. The first chapter looks at the effects of a change in the regulation governing oceanic goods trade, the IMSBC code, on the international trade in commodities. The second chapter investigates how trade liberalisation affects the mode of transport, using the removal of quotas under the Multi-Fibre Arrangement to study its effects on the modal decisions of Chinese firms. The final chapter uses firm-level panel data to look at the effect of the feedin-tariff on renewable energy firms’ performance in the UK.